2008
DOI: 10.1101/gad.1709008
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ and C/EBP factors orchestrate adipocyte biology via adjacent binding on a genome-wide scale

Abstract: Peroxisome proliferator-activated receptor ␥(PPAR␥), a nuclear receptor and the target of anti-diabetic thiazolinedione drugs, is known as the master regulator of adipocyte biology. Although it regulates hundreds of adipocyte genes, PPAR␥ binding to endogenous genes has rarely been demonstrated. Here, utilizing chromatin immunoprecipitation (ChIP) coupled with whole genome tiling arrays, we identified 5299 genomic regions of PPAR␥ binding in mouse 3T3-L1 adipocytes. The consensus PPAR␥/RXR␣ "DR-1"-binding moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

51
707
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 732 publications
(764 citation statements)
references
References 65 publications
51
707
1
5
Order By: Relevance
“…Of note, both MED1 clusters coincide with binding peaks for PPARγ and C/EBPβ, two master transcriptional regulators of adipogenesis. 64 Future work will be aimed at validating the functional role of these and other genomic regions in adipogenesis-induced Cd274 / Pd-l1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, both MED1 clusters coincide with binding peaks for PPARγ and C/EBPβ, two master transcriptional regulators of adipogenesis. 64 Future work will be aimed at validating the functional role of these and other genomic regions in adipogenesis-induced Cd274 / Pd-l1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…81 Peroxisome proliferator-activated receptor-g (PPAR gamma), CCAAT/enhancer-binding protein (C/EBP) and sterol-regulatory element-binding protein-1 (SREBP-1) are also involved in adipose tissue differentiation and act as transcriptional regulators to modulate gene expression and the functional proteins related to adipose function. [82][83][84][85][86] Some investigators have found that 1,25-dihydroxyvitamin D 3 appears to block adipose tissue differentiation by suppressing LPL, aP2, C/EBP-a, PPAR-g and SREBP-1. 76,77 There is controversy, however.…”
Section: Methodsmentioning
confidence: 99%
“…1C). We chose to study C/EBPα in more detail because it is involved in the activation of differentiation in several cell types (15), including keratinocytes (16)(17)(18) and adipocytes (19)(20)(21), potentially linking C/EBPα binding to methylated promoters with activation of methylated promoters upon differentiation (see below).…”
mentioning
confidence: 99%